Implementing the problem-based learning model to improve students' mathematical problem-solving ability - Shinta, Putri; Sakur; Heleni, Susda (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This research addresses the low level of mathematical problem-solving ability among eighth-grade students of MTs PP Nurul Islam Kampung Baru, class VIII.1. The study aims to enhance the learning process and improve students' mathematical problem-solving skills through the application of the problem-based learning model. Conducted as Classroom Action Research, the study was carried out in two cycles, each comprising the stages of planning, implementation, observation, and reflection. The research involved 30 students from class VIII.1 as participants. Data collection was performed using observation and mathematical problem-solving tests. The findings revealed an improvement in students' problem-solving abilities, with average scores increasing from 26.5 in the initial test to 52.33 in the first cycle and 65.5 in the second cycle. These results demonstrate that implementing the problem-based learning model effectively enhances both the learning process and students' mathematical problem-solving skills at MTs PP Nurul Islam Kampung Baru.